2021
DOI: 10.2340/16501977-2854
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and validity of a standardised ultrasound examination protocol to quantify vastus lateralis muscle

Abstract: Objective To evaluate the reliability and validity of a standardized ultrasound examination protocol for measuring vastus lateralis muscle size. Design Prospective cohort study. Subjects Sixteen staff members of the university hospital of Heidelberg. Methods Muscle thickness, cross-sectional area and subcutaneous adipose tissue thickness were measurxsed at 3 standardized sites on the right and left vastus lateralis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 26 publications
(25 reference statements)
3
17
0
Order By: Relevance
“…The ICC values varied for the different muscles; however, the confidence intervals were overlapping. The current study presents a good to excellent inter-rater reliability, in line to those of previous studies ( Tillquist et al, 2014 ; Zaidman et al, 2014 ; Hadda et al, 2017 ; Filippo et al, 2019 ; Mechelli et al, 2019 ; Betz et al, 2021 ; Takahashi et al, 2021 ). However, variations in methodology including site(s), time in-between measurements and number of measurements make direct comparisons difficult.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The ICC values varied for the different muscles; however, the confidence intervals were overlapping. The current study presents a good to excellent inter-rater reliability, in line to those of previous studies ( Tillquist et al, 2014 ; Zaidman et al, 2014 ; Hadda et al, 2017 ; Filippo et al, 2019 ; Mechelli et al, 2019 ; Betz et al, 2021 ; Takahashi et al, 2021 ). However, variations in methodology including site(s), time in-between measurements and number of measurements make direct comparisons difficult.…”
Section: Discussionsupporting
confidence: 92%
“…An accurate determination of skeletal muscle mass is of great importance when investigating muscle adaptation during hypertrophy ( Aagaard et al, 2001 ; Morse et al, 2005 ; D'Antona et al, 2006 ; Franchi et al, 2018 ) and atrophy ( Abe et al, 1997 ; LeBlanc et al, 2000 ; Alkner and Tesch, 2004 ; Maurits et al, 2004 ; Rittweger et al, 2005 ; Petterson et al, 2008 ; Dirks et al, 2016 ; Johnson et al, 2018 ). Several methods for assessing or estimating skeletal muscle size have been described including bioimpedance ( Salinari et al, 2002 ), computerized tomography ( Van Roie et al, 2013 ), magnetic resonance imaging (MRI) ( Walton et al, 1997 ; Alkner and Tesch, 2004 ; Nordez et al, 2009 ) and ultrasound (US) ( Miyatani et al, 2002 ; Miyatani et al, 2004 ; Reeves et al, 2004 ; Sanada et al, 2006 ; Moreau et al, 2010 ; Baldwin et al, 2011 ; Scott et al, 2012 ; Strasser et al, 2013 ; Tillquist et al, 2014 ; Fukumoto et al, 2015 ; Giles et al, 2015 ; Nakatani et al, 2016 ; Hadda et al, 2017 ; Matta et al, 2017 ; Stock et al, 2017 ; Franchi et al, 2018 ; Pardo et al, 2018 ; Filippo et al, 2019 ; Mechelli et al, 2019 ; Cheon et al, 2020 ; Betz et al, 2021 ; Lee et al, 2021 ; Mpampoulis et al, 2021 ; Takahashi et al, 2021 ). Muscle volume (MV) estimated from multiple cross-sectional areas (CSA) using MRI is considered the current gold standard, however, this process is time consuming and labor-intensive ( Nordez et al, 2009 ), therefore the feasibility of MRI is limited, especially for repeated measurements in large cohorts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, reported agreement in validation studies of ultrasonography based muscle architecture assessment using cadaveric dissection was higher as well (Bénard et al, 2009;Kellis et al, 2009). In terms of test-retest reliability of ultrasonographic architecture assessment in all here investigated muscles, ICCs between 0.7 and 0.98, 0.7 to 0.98 and 0.74 to 0.99 have been reported for muscle thickness, fascicle length, and pennation angle, respectively (Narici et al, 2003;Blazevich et al, 2006;Ema et al, 2013;Bolsterlee et al, 2015;Trezise et al, 2016;Geremia et al, 2019;Nijholt et al, 2020;Betz et al, 2021;May et al, 2021;Hagoort et al, 2022). Reported SEM% were between 0.6 and 4.8%, 2-18.9%, and 4.3-23% for muscle thickness, fascicle length, and pennation angle, respectively (Narici et al, 2003;Bénard et al, 2009;Ema et al, 2013;Bolsterlee et al, 2015;Trezise et al, 2016;Oranchuk et al, 2020;May et al, 2021;Hagoort et al, 2022).…”
Section: Figuresupporting
confidence: 58%
“…Accordingly, a high concordance between measurement procedures with very low measurement error is mandatory to rule out the possibility that measured changes could be explained due to measurement error. To investigate MT, sonography is commonly used (Sarto et al, 2021) and is described as a valid and reliable assessment with inter-day reliability of an intraclass correlation coefficient (ICC) of 0.72-0.99 (Wong et al, 2013;Rosenberg et al, 2014) and intra-day reliability of ICC = 0.97-0.99 in the multifidus lumborum and the gastrocnemius muscle, as well as very high inter-rater-and intra-rater reliability of ICC = 0.78-0.94 (Wallwork et al, 2007;Teyhen and Koppenhaver, 2011;Chiaramonte et al, 2019;Betz et al, 2021) measured in the quadriceps and multifidus muscle. However, reviews by English et al (2012) and Hebert et al (2009) only showed moderate reliability for intra-and interday reliability (ICC = 0.62-0.97) when investigating muscle size via sonography.…”
Section: Introductionmentioning
confidence: 99%